Analyzing urban spatial patterns and trend of urban growth using urban sprawl matrix: A study on Kolkata urban agglomeration, India - Sahana, Mehebub; Hong, Haoyuan; Sajjad, Haroon (The Science of the total environment, 2018)
This research paper analyzed urban spatial pattern and trend of urban growth in Kolkata urban agglomeration, India using urban sprawl matrix during 1990–2000 & 2000–2015. Seven urban classes viz. urban primary core, urban secondary core, sub urban fringe, scatter settlement, urban open space, non-urban area and water body were chosen for analyzing the magnitude and direction of urban expansion. Landsat TM and Landsat 8 OLI satellite data for 1990, 2000 and 2015 were used for assessing land use land cover change, urban land transformation, urban spatial pattern and trend in urban growth. The study revealed that the built up area has increased drastically. This increase in built up area is attributed to decrease in prime agricultural land and open space. The land use/land cover change matrix showed that built up area has expanded by 16.6% during 1990–2000 and 24.5% during 2000–2015. The urban expansion is a result of large share of land transformation from agricultural land at the rate of 153.1% during 1990–2000 and 66.9% during 2000–2015. Analysis of trend of urban growth in 38 municipalities and 3 municipal corporations of Kolkata urban agglomeration revealed that municipalities located along the east bank of river Hooghly and surrounded by Kolkata Municipal Corporation have experienced a very fast urban growth. Urban primary and secondary cores have increased in newly developed municipalities. Sub urban fringe has increased in the municipalities located away from river Hooghly while open space has decreased in all the old municipalities. Pattern of land transformation and trend of urban growth of Kolkata urban agglomeration for the last 25years may help in guiding future planning and policy-making for the urban agglomeration. Integrated approach of remote sensing, GIS and urban sprawl matrix has proved instrumental in analyzing urban expansion and identifying priority areas for effectives planning and management. [Display omitted] •Sprawl matrix was used to analyze urban patterns and growth in an urban agglomeration.•Suburban fringe has increased within the municipalities located away from the river.•Urban primary and secondary cores have increased in newly developed municipalities.•The methodology adopted has proved instrumental for urban planning and management.